Rhodol‐derived turn‐on fluorescent probe for copper ions with high selectivity and sensitivity. (5th August 2021) - Zeng, Xiaodan; Gao, Song; Jiang, Cheng; Duan, Qingxia; Ma, Mingshuo; Liu, Zhigang; Chen, Jie
Abstract: A new rhodol‐derived fluorescent probe 1 with picolinate as the recognition receptor was designed and simply synthesized using a one‐step reaction. With the concentration of added Cu 2+ increases, it gradually turns pink, so the effect of naked eye detection can be achieved. The detection limit of probe 1 for Cu 2+ is 42 nM, and the linear detection range was 0–2 μM. The experimental results showed that 1 was a fluorescent probe with high selectivity, good water solubility, and high sensitivity to Cu 2+ . Probe 1 was successfully applied in cell imaging experiments and can detect the concentration of Cu 2+ in water samples. All these indicate that probe 1 has the potential to be applied to the detection of Cu 2+ concentration in the real environment. Abstract : A rhodol‐derived fluorescent probe for Cu 2+ ions was designed and simply synthesized by a one‐step reaction. The rhodol‐derived fluorescent probe exhibited high selectivity and sensitivity. The fluorescence imaging of living cells shows the applications of the probe in biosystems.